Muzakki’s enthusiasm towards the use of productive zakat on financing free halal certification for micro and small enterprises - Hasanah, Neneng; Putri, Uly Anggraeni; Aisyah, Tasya Nur; Anggini, Karlita; Priyanto, Anindia Meil; Irfany, Mohammad iqbal (IPB University, 2024)
The cost of obtaining halal certification is often significant, and this has made its obtainance difficult for many Micro and Small Enterprises (MSEs). In order to promote the attainment of halal certification, the government has been observed to offer free certification programs for MSEs, with expenses being totally covered by the State Budget (APBN). Based on the results, alternative sources of financing beyond the state budget are necessary, with productive zakat being a plausible option. Therefore, the present study aims to assess the willingness of Muzakki to use productive zakat to finance free halal certification for MSEs and to analyze the factors influencing this willingness. To achieve the stated objectives, scoring and Structural Equation Models, namely Partial Least Square (SEM-PLS), were adopted as the analytical methods. Data were collected via electronic questionnaires administered to 200 respondents who had previously contributed mal zakat, and interviews conducted with representatives from BAZNAS. The obtained results showed that a positive inclination existed among Muzakki to use productive zakat for financing halal certification for MSEs. The observed key factors influencing enthusiasm of Muzakki include external motivation and consistency in zakat contributions. To enhance the role of zakat, the study suggests that zakat institutions should prioritize information dissemination and awareness campaigns through various media channels.